2011
DOI: 10.1089/ars.2010.3640
|View full text |Cite
|
Sign up to set email alerts
|

Protein Carbamylation Renders High-Density Lipoprotein Dysfunctional

Abstract: Aim-Carbamylation of proteins through reactive cyanate has been demonstrated to predict an increased cardiovascular risk. Cyanate is formed in vivo by break-down of urea and at sites of inflammation by the phagocyte protein myeloperoxidase. Since myeloperoxidase (MPO) associates with high-density lipoprotein (HDL) in human atherosclerotic intima, we examined in the present study whether cyanate specifically targets HDL.Results-Mass spectrometry analysis revealed that protein carbamylation is a major posttransl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
4
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(149 citation statements)
references
References 38 publications
8
131
4
5
Order By: Relevance
“…139 Intriguingly, HDL isolated from human atherosclerotic lesions carried high amounts of carbamyllysines. 140,141 These results are consistent with the assumption that HDL trapped in the vascular wall becomes a target for carbamylation. In vitro carbamylation by the MPO/thiocyanate/H2O2 system or cyanate has been shown to transform HDL into proatherosclerotic particles.…”
Section: Protein Carbamylationsupporting
confidence: 87%
See 1 more Smart Citation
“…139 Intriguingly, HDL isolated from human atherosclerotic lesions carried high amounts of carbamyllysines. 140,141 These results are consistent with the assumption that HDL trapped in the vascular wall becomes a target for carbamylation. In vitro carbamylation by the MPO/thiocyanate/H2O2 system or cyanate has been shown to transform HDL into proatherosclerotic particles.…”
Section: Protein Carbamylationsupporting
confidence: 87%
“…139 Also, HDL particles modified through carbamylation not only had poorer cholesterol efflux activities, but instead facilitated further accumulation of cholesterol in human monocytes. 140 Another important observation is that cyanate-treated HDL had lower LCAT activity. 141 Additional studies demonstrated that carbamalytion reduced the activity of PON1 within HDL and hence the concomitant antioxidative effects of HDL against LDL oxidation.…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…It is notable that multiple alternative receptors exist for interaction with carbamylated proteins. For example, it has recently been reported that HCit on apolipoprotein A1 of carbamylated high density lipoprotein confers recognition by scavenger receptor class B, type 1 (SRARB1), and macrophage foam cell formation (77). Yet additional recent studies have suggested that the class E scavenger receptor lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) in human vein endothelial cells can also recognize and bind carbamylated low density lipoprotein, leading to increased reactive oxygen species generation and increased cellular apoptosis (78).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic oxidative stress, inflammation, and uraemia lead to oxidation, carbamylation, and myeloperoxidase-mediated modification of ApoA-1 and other protein constituents of HDL. Such modifications to ApoA-1 have been shown to impair HDL-mediated reverse cholesterol transport and promote atherosclerosis by limiting the binding of HDL to its receptors, including ABCA-1 [74][75][76][77] . These processes can in part account for atherogenic diathesis in this population, and oxidative modification of HDL has been demonstrated in patients with ESRD 78,79 .…”
Section: Upregulation Of Acatmentioning
confidence: 99%